Pesticides And Farmer Health In Nicaragua: A Willingness To Pay Approach - Hermann Waibel; Hildegard Garming (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2007)
This study presents an economic valuation of health risks of pesticides among Nicaraguan vegetable farmers. A comprehensive valuation of market and non-market value components of human health is established through farmers? willingness to pay (WTP) for low toxicity pesticides. Results show, that farmers are willing to spend about 28% of current pesticide expenditure for avoiding health risks. The validity of results is established in scope tests and a two-step regression model. WTP depends on farmers? experience with poisoning, income variables and pesticide exposure. The results can help in targeting of rural health policies and the design of programmes aiming to reduce negative effects of pesticides.
Keywords: 330; Health risks of pesticides; Contingent Valuation; Nicaragua